2021
DOI: 10.1089/jwh.2021.29037
|View full text |Cite
|
Sign up to set email alerts
|

International Society for the Study of Women's Sexual Health Clinical Practice Guideline for the Use of Systemic Testosterone for Hypoactive Sexual Desire Disorder in Women

Abstract: Background:The Global Consensus Position Statement on the Use of Testosterone Therapy for Women (Global Position Statement) recommended testosterone therapy for postmenopausal women with hypoactive sexual desire disorder (HSDD). Aim: To provide a clinical practice guideline for the use of testosterone including identification of patients, laboratory testing, dosing, post-treatment monitoring, and follow-up care in women with HSDD. Methods: The International Society for the Study of Women's Sexual Health appoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 153 publications
(165 reference statements)
0
16
0
1
Order By: Relevance
“…There is a constant evolution, reflected in the short-time between actualizations of these statements [ 481 , 646 , 647 , 648 , 649 ]; but the use of TRT for aging (and/or MS-derived hypogonadism) keeps growing [ 650 ]. The focus is now shifting to the discussed and controversial use of TRT in women [ 651 , 652 , 653 ], which may be related to the deeply ingrained (and scientifically unjustifiable) notion that sex hormones fully imply an “absolute” link to gender: androgen for males and estrogen for females, with no space in between. This unproved belief has been a pillar of “sex hormone medical knowledge”, and remains true up to the present for generations of physicians, scientists and social leaders and activists.…”
Section: The Use Of Androgens For the Treatment Of Functional Disordersmentioning
confidence: 99%
“…There is a constant evolution, reflected in the short-time between actualizations of these statements [ 481 , 646 , 647 , 648 , 649 ]; but the use of TRT for aging (and/or MS-derived hypogonadism) keeps growing [ 650 ]. The focus is now shifting to the discussed and controversial use of TRT in women [ 651 , 652 , 653 ], which may be related to the deeply ingrained (and scientifically unjustifiable) notion that sex hormones fully imply an “absolute” link to gender: androgen for males and estrogen for females, with no space in between. This unproved belief has been a pillar of “sex hormone medical knowledge”, and remains true up to the present for generations of physicians, scientists and social leaders and activists.…”
Section: The Use Of Androgens For the Treatment Of Functional Disordersmentioning
confidence: 99%
“…ISSWSH has published a clinical practice guideline, informed by a Global Consensus Position Statement 9 developed by 11 international medical societies, including The North American Menopause Society, on the use of testosterone therapy in women that supports the use of systemic transdermal testosterone therapy for postmenopausal and late-reproductive-aged women with HSDD 10 . Recommended formulations are approved transdermal products for men using approximately one-tenth of the dose for men, with the targeted goal of the physiologic premenopause range.…”
Section: Medicationsmentioning
confidence: 99%
“…Dehydroepiandrosterone (DHEA, 3β-hydroxy-5-androstene-17-one) is an important cholesterol-derived intermediate that function both as the major steroid hormone with systemic endocrine function in humans, and as a food supplement or drug approved by FDA [ 15 18 ]. Our and other researchers found that DHEA has anti-inflammation and anti-oxidant activities in several mouse inflammatory model [ 19 21 ], which implied that it can be used as a potential anti-inflammatory supplemental agent.…”
Section: Introductionmentioning
confidence: 99%